2019
DOI: 10.1038/s41598-019-42183-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term benefit of Microbiota Transfer Therapy on autism symptoms and gut microbiota

Abstract: Many studies have reported abnormal gut microbiota in individuals with Autism Spectrum Disorders (ASD), suggesting a link between gut microbiome and autism-like behaviors. Modifying the gut microbiome is a potential route to improve gastrointestinal (GI) and behavioral symptoms in children with ASD, and fecal microbiota transplant could transform the dysbiotic gut microbiome toward a healthy one by delivering a large number of commensal microbes from a healthy donor. We previously performed an open-label trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
406
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 533 publications
(425 citation statements)
references
References 53 publications
11
406
1
7
Order By: Relevance
“…[69][70][71] Conversely, several commensal bacteria with lower relative abundance are known to induce anti-inflammatory effects 72,73 or are involved in the maintenance of normal metabolism. 64,[73][74][75] The findings have been supported by Rose et al 47 and Carissimi et al, 51 who reported that ASD cases had an increased concentration of pro-inflammatory cytokines. However, we still lack more in-depth analyzes in the functions affected by the gut microbiota in ASD.…”
Section: Gut Microbiota Of Asd And/or Adhdmentioning
confidence: 61%
“…[69][70][71] Conversely, several commensal bacteria with lower relative abundance are known to induce anti-inflammatory effects 72,73 or are involved in the maintenance of normal metabolism. 64,[73][74][75] The findings have been supported by Rose et al 47 and Carissimi et al, 51 who reported that ASD cases had an increased concentration of pro-inflammatory cytokines. However, we still lack more in-depth analyzes in the functions affected by the gut microbiota in ASD.…”
Section: Gut Microbiota Of Asd And/or Adhdmentioning
confidence: 61%
“…Moreover, clinical assessments showed a slow but steady improvement in core ASD symptoms, and the improvements were sustained after an eight-week follow-up observation period [46]. Remarkably, in a recent follow-up with the same 18 participants, two years after treatment, GI benefits were mostly maintained and autism-related symptoms improved even more [47].…”
Section: Gut Microbiota: Dysbiosis and Therapeutic Potential In Asdmentioning
confidence: 88%
“…In another study, microbiota transfer therapy (MTT) was used to treat autism-like behaviors. Kang et al found improvement in behavioral symptoms in autistic children when the children received transplanted commensal microbes from healthy donors [90].…”
Section: The Microbiota and Psychiatric Disordersmentioning
confidence: 99%